BASALT FIBER GRAVEL - SCIENTIFIC-METHODICAL PRINCIPLES OF CREATION OF ROCK STONE COVERING MATERIALS (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the scientific article, the opinions of foreign scientists were studied in order to obtain basalt-fiber gravel-rock composite compounds. Proposals and recommendations are given on the scientific and methodological bases of the production of basalt fibrous gravel-stone products.